Peningkatan Kreativitas Guru Melalui Penguatan Efektivitas Pelatihan, Literasi Digital, Dan Efikasi Diri - Kusyanti, Ela; Hendarman, Hendarman; Suhardi, Eka (Universitas Pakuan, 2024)
IMPROVING TEACHERS' CREATIVITY THROUGH TRAINING EFFECTIVENESS, DIGITAL LITERACY, AND SELF-EFFICACYThe development of the world of education today requires teachers to be more creative and innovative. The development of ideas or ideas and creative teacher learning behavior is an essential factor in achieving adequate educational outcomes. Creative teachers will impact the organization and change the work environment positively. This study aims to find ways to increase teacher creativity by analyzing the influence of other variables. Data analysis used structural equation modeling (SEM) by conducting two tests, namely, the evaluation of the measurement model and the evaluation of the structure model. The research results show that; (a) training effectiveness has a positive effect on teacher creativity with a path coefficient value of (βyx1=0.296), (b) digital literacy has a positive effect on teacher creativity with a path coefficient value of (βyx2=0.050), (c) self-efficacy has a positive effect on teacher creativity with a path coefficient value of (βyx3=0.553), (d) training effectiveness has a positive effect on self- efficacy with a path coefficient value of (βx3x1=0.394), (e) digital literacy has a positive effect on self-efficacy with a path coefficient value of ( βx3x2=0.267), (f) there is an indirect positive effect between the effectiveness of training on teacher creativity through self- efficacy of (βx31Y=0.218), and (g) there is an indirect positive effect between digital literacy on teacher creativity through self- efficacy of (βx31Y = 0.147) means that the results of the structural model evaluation show a positive influence between training effectiveness, digital literacy d and self-efficacy on teacher creativity.